Corrected orthogonal vectorcardiography in pulmonary hypertension diagnostics - E. S. Yurasova; T. A. Sakhnova; I. E. Chazova; N. A. Tsareva; S. N. Avdeev; O. Yu. At’kov (Кардиоваскулярная терапия и профилактика)
Aim. To assess potential of corrected orthogonal vectorcardiography (VCG) in diagnostics of right heart dilatation in various pulmonary hypertension (PH) forms. Material and methods. VCG examination was performed with corrected orthogonal lead system by MacFeeParungao, in 77 patients aged 14-77 years: 35 individuals with primary PH (PPH), 42 participants with secondary PH (CPH) due to congenital and acquired valve disease (CVD, AVD), or chronic obstructive pulmonary disease (COPD). Results. According to VCG results, right atrium dilatation was observed in 80.5% of PH patients, right ventriculum dilatation – in 90.9%. Prevalence of right heart dilatation was maximal in PPH – 94.3%, being lower in COPD (80%), CVD, and AVD (59.1%). VCG predictors of right heart dilatation in PH were: P loop spatial area, P loop diameter in optimal approach plane, and total R wave amplitude regarding z and S in lead x. Conclusion. According to the results obtained, VCG method could be recommended for right heart size assessment in patients with various PH forms.